KORELASI FAKTOR PSIKOLOGI DAN GAYA HIDUP DENGAN KETUBAN PECAH DINI : Correlation of Psychological Factors and Lifestyle with Premature Rupture of Membranes - Ayu Anulus; Artha Budi Susila Duarsa; I Gede Ari Permana Putra; Aris Widiyanto; Joko Tri Atmojo (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Premature rupture of membranes (PRM) can occur at the end of pregnancy or long before it is time to give birth. Psychological factors within the mother can include the mother's personality background and the influence of hormonal changes that occur during pregnancy. In relation to PRM, the lifestyle referred to is the lifestyle of pregnant women which can have negative effects on their babies and themselves. This research aims to determine the correlation between psychological and lifestyle factors and PROM. This was an analytical observational study with a quantitative approach. The research was conducted in March-May 2022. The independent variables in this research include psychological and lifestyle factors. The dependent variable in this study is premature rupture of membranes (PRM). The sampling technique used was total sampling. The sample in this study was all 30 mothers who experienced premature rupture of membranes at the Wahyu Husada Clinic. The analysis technique in this study used Pearson correlation. The results showed that psychology (r = 0.56) and lifestyle (r = 0.62) were correlated with premature rupture of membranes and were statistically significant.